2015
DOI: 10.1021/acs.biochem.5b00003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reduced Rhodopsin Expression on the Structure of Rod Outer Segment Disc Membranes

Abstract: Rhodopsin is the light receptor embedded in rod outer segment (ROS) disc membranes of photoreceptor cells that initiates vision via phototransduction. The relationship between rhodopsin expression and the formation of membrane structures in the ROS is unclear but important to better understand both normal function and pathological conditions. To determine the impact of reduced rhodopsin expression on the structure of ROS discs and the supramolecular organization of rhodopsin, ROS disc membrane samples from het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(90 citation statements)
references
References 49 publications
6
84
0
Order By: Relevance
“…Mice used in previous AFM studies were housed in a standard cyclic 12 h light and 12 h dark lighting environment [40, 50]. To examine the impact of environmental lighting on the structure of ROS disc membranes, C57Bl/6J mice were housed in constant light or constant darkness for 10 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice used in previous AFM studies were housed in a standard cyclic 12 h light and 12 h dark lighting environment [40, 50]. To examine the impact of environmental lighting on the structure of ROS disc membranes, C57Bl/6J mice were housed in constant light or constant darkness for 10 days.…”
Section: Resultsmentioning
confidence: 99%
“…ROS disc membrane samples were prepared on freshly cleaved mica and imaged by AFM as described previously [49]. Contact mode AFM imaging was performed in imaging buffer (20 mM Tris, 150 mM KCl, 25m MgCl 2 , pH 7.8) using a Veeco Multimode II atomic force microscope equipped with an E scanner and DNP-S silicon nitride cantilevers with a nominal spring constant of 0.06 N/m (Bruker Corporation, Santa Barbara, CA), as described previously [50]. Deflection AFM images were analyzed using SPIP software (version 6.4, Image Metrology A/S, Hørsholm, Denmark) to measure ROS disc membrane properties, as described previously [50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study used electron microscopy on the retina of T. proximus and showed that the membrane discs unique to rods in the outer segment are still present in the transmuted photoreceptor (Schott et al, 2016). Interestingly, a reduction of RH1 expression levels has been shown to reduce the size of the outer segment of rods, in addition to lowering the photosensitivity and altering the kinetics of the cell to be more cone-like (Makino et al, 2012;Rakshit and Park, 2015;Wen et al, 2009). Currently, the relative expression levels of RH1 in the retinas of colubrid snakes have not been measured.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theoretical work has proposed that the small tapering outer segments of cones may help to reduce self-screening of the visual pigments, increase signal-to-noise ratios, and allow light to more efficiently be focused on the outer segment by the ellipsoid (35). Interestingly, recent work has also suggested that reduction of RH1 expression alone can result in a more cone-like morphology, decreasing the photosensitivity of the cell and increasing the kinetics of the phototransduction cascade (34,36,37). A second striking difference in rod and cone morphology is the accessibility of the outer-segment discs to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%